Human Resources Management in the Posture Development of the Indonesian National Armed Forces for National Defence - Philip Jeremia Sinaga; Hikmat Zakky Almubaroq; Agus Sudarya (CV. AFDIFAL MAJU BERKAH, 2023)
Human resources are the most important assets possessed by every institution, from the lowest level of institutions to the highest level such as the state. The dynamics of an uncertain and complex strategic environment have an impact on the defense posture of the TNI, which continues to be demanded to be able to balance these dynamics. In the process, the development of the TNI's posture experienced many obstacles, so that the role of human resource management (HR) was needed in developing the posture of the Indonesian National Armed Forces (TNI) for national defense purposes. Through a qualitative approach and data collection from primary and secondary sources, this study analyzes various aspects of human resource management that are relevant in the context of the TNI. The results of this study indicate that there are still problems in every process of human resource management in the development of the TNI's posture, such as welfare, health services, and social security. Based on these problems, the role of human resource management is needed according to the needs and dynamics of the existing strategic environment. The findings of this journal can provide insight into how effective human resource management can influence national defense forces and enhance TNI capabilities.